Case report: Fully endoscopic microvascular decompression for trigeminal neuralgia - Jiang, Haotian; Zou, Dewei; Wang, Pan; Zeng, Longwei; Liu, Jie; Tang, Chao; Zhang, Gang; Tan, Xiaorong; Wu, Nan (Frontiers in Neurology, 2023)
Microvascular decompression is safe, effective, and micro-invasive. Due to these advantages, it has become the mainstream treatment for trigeminal neuralgia, glossopharyngeal neuralgia, and hemifacial spasm. Initially, microvascular decompression was performed under a microscope, which limited the light source and visualization capabilities. With the development of endoscopic technology, the endoscope has been used in microvascular decompression, which further improved the visualization range and light source properties. The purpose of the present study was to investigate the efficacy of fully endoscopic microvascular decompression for the treatment of trigeminal neuralgia. In total, three patients with trigeminal neuralgia who underwent fully endoscopic microvascular decompression were evaluated. After surgery, the facial pain of all patients was significantly relieved. In addition, there were no obvious postoperative complications and no recurrence after 6 months of follow-up. These excellent surgical outcomes indicate that fully endoscopic microvascular decompression is an effective and safe method for the treatment of trigeminal neuralgia. Furthermore, it also shows that the endoscope presents advantages for use in microvascular decompression.